Employability challenges of vocational college graduates in the state of Johor - Kiong, Tee Tze; Zulkifli, Mohamad Azim Nashraf Bin (Jurnal Pendidikan Teknologi Kejuruan, 2024)
The purpose of this research is to determine the difficulties experienced by Vocational College (VC) graduates in selecting a job, aligning their study program with the career, and figuring out the abilities that employers want depending on factors such as gender, study program, and VC after graduation. 234 graduates of Electrical Technology, Electronic Technology, Welding Technology, Construction Technology, and Automotive Technology programs from 2020 to 2022 VC in Johor participated in the study. This study used a quantitative survey research approach, utilizing a questionnaire and simple random sampling to analyze data both descriptively and inferentially against a sample representative of the total population. The findings demonstrated that graduates have significant difficulties selecting a vocation, determining if their study program is suitable, and determining what qualities companies are looking for. The results of the Mann-Whitney U and Kruskal Wallis tests showed that there is gender-based variations in the abilities and problems associated with choosing a vocation. The degree of difficulty in matching studies with jobs, compatibility of studies with careers, and the abilities employers want depending on the study program did not change based on a person's gender. Finally, depending on VC, notable variations were discovered in the degree of career choices, program fit, and skills needed by employers.